2017
DOI: 10.1007/s11356-017-8428-4
|View full text |Cite
|
Sign up to set email alerts
|

The nexus of oil consumption, CO2 emissions and economic growth in China, Japan and South Korea

Abstract: This article attempts to explore the nexus between oil consumption, economic growth and carbon dioxide (CO) emissions in three East Asian oil importing countries (i.e. China, South Korea and Japan) over the period 1980-2013, by using the Granger causality, Johansen cointegration test, Generalised Impulse Response functions (GIRF) and variance decompositions. The empirical findings provide evidence for the existence of a long-run relationship between oil consumption and economic growth in China and Japan. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 128 publications
(38 citation statements)
references
References 94 publications
3
28
1
1
Order By: Relevance
“…In terms of increased energy demand, the issue of global warming, and the potential for developing green energy resources in Asia, there is a question of how macroeconomic variables can accelerate or decelerate energy transition movement in different regions in Asia. Despite numerous studies such as Fattouh et al (2019); Yuan et al (2018), Sharvini et al (2018); Aung et al (2017), Saboori et al (2017); Taghizadeh-Hesary et al 2016Taghizadeh-Hesary et al 2017; Reddy (2016), and Hess and Mai (2014) focusing on energy consumption and energy transition in Asian countries, we did not find any serious academic research considering energy transition patterns among such countries. Hence, this point covers the major novelty of our research and the gap in the literature our findings may fill.…”
Section: Introductioncontrasting
confidence: 60%
“…In terms of increased energy demand, the issue of global warming, and the potential for developing green energy resources in Asia, there is a question of how macroeconomic variables can accelerate or decelerate energy transition movement in different regions in Asia. Despite numerous studies such as Fattouh et al (2019); Yuan et al (2018), Sharvini et al (2018); Aung et al (2017), Saboori et al (2017); Taghizadeh-Hesary et al 2016Taghizadeh-Hesary et al 2017; Reddy (2016), and Hess and Mai (2014) focusing on energy consumption and energy transition in Asian countries, we did not find any serious academic research considering energy transition patterns among such countries. Hence, this point covers the major novelty of our research and the gap in the literature our findings may fill.…”
Section: Introductioncontrasting
confidence: 60%
“…We found that world energy prices have a non-linear impact on total CO 2 emissions. These findings align with the study by Lim, Lim, and Yoo (2014), Nwani (2017), Saboori, Rasoulinezhad, and Sung (2017) and Ahmad et al (2018). They also found that oil-dependent countries do not change Table 7.…”
Section: Resultssupporting
confidence: 90%
“…But OPt depicted a significant negative relationship with CO2t at 1 percent level of significance and the elasticity parameter described that 1 percent rise in OPt will bring about 0.4379 percent decrease in CO2t in the long-run. The finding supports the assumption that revenue realized from crude oil exports are employed in maintaining the environmental quality and the finding corroborate the empirical outcomes of Saboori, Rasoulinezhad, and Sung (2017) for Japan and China.…”
Section: Ardl Bounds Test Resultssupporting
confidence: 84%